Ubiquitination and the Proteasome as Drug Targets in Trypanosomatid Diseases - Bijlmakers, Marie-José (Frontiers in Chemistry, 2021)
The eukaryotic pathogens Trypanosoma brucei, Trypanosoma cruzi and Leishmania are responsible for debilitating diseases that affect millions of people worldwide. The numbers of drugs available to treat these diseases, Human African Trypanosomiasis, Chagas' disease and Leishmaniasis are very limited and existing treatments have substantial shortcomings in delivery method, efficacy and safety. The identification and validation of novel drug targets opens up new opportunities for the discovery of therapeutic drugs with better efficacy and safety profiles. Here, the potential of targeting the ubiquitin-proteasome system in these parasites is reviewed. Ubiquitination is the posttranslational attachment of one or more ubiquitin proteins to substrates, an essential eukaryotic mechanism that regulates a wide variety of cellular processes in many different ways. The best studied of these is the delivery of ubiquitinated substrates for degradation to the proteasome, the major cellular protease. However, ubiquitination can also regulate substrates in proteasome-independent ways, and proteasomes can degrade proteins to some extent in ubiquitin-independent ways. Because of these widespread roles, both ubiquitination and proteasomal degradation are essential for the viability of eukaryotes and the proteins that mediate these processes are therefore attractive drug targets in trypanosomatids. Here, the current understanding of these processes in trypanosomatids is reviewed. Furthermore, significant recent progress in the development of trypanosomatid-selective proteasome inhibitors that cure mouse models of trypanosomatid infections is presented. In addition, the targeting of the key enzyme in ubiquitination, the ubiquitin E1 UBA1, is discussed as an alternative strategy. Important differences between human and trypanosomatid UBA1s in susceptibility to inhibitors predicts that the selective targeting of these enzymes in trypanosomatids may also be feasible. Finally, it is proposed that activating enzymes of the ubiquitin-like proteins SUMO and NEDD8 may represent drug targets in these trypanosomatids as well.